The Diminishing Effect of Transformational Leadership on the Relationship Between Task Characteristics, Perceived Meaningfulness, and Work Engagement - Meng, Fanxing; Wang, Yi; Xu, Wenying; Ye, Junhui; Peng, Lin; Gao, Peng (Frontiers in Psychology, 2020)
The topic of employee work engagement in the public sector has attracted broad attention because it is critical to the efficiency and effectiveness of public services. Based on the Job Characteristics Model (JCM) and the Integrative Theory of Employee Engagement (ITEE), the present research adopts a multilevel design to examine a moderated mediation model in which task characteristics (i.e. task autonomy and task significance as level-1 predictors) and social context (i.e. transformational leadership as a level-2 moderator) jointly impact employee work engagement via individual perception of meaningfulness in work. A total of 349 grassroots police officers from 35 police substations were invited to anonymously complete a survey via mobile app. After performing the cross-sectional analysis, the results indicated that in contrast to task significance, the conditional effect of task autonomy on work engagement via perceived meaningfulness was more positive at a lower level of transformational leadership. Implications, limitations, and future research directions are discussed.